Association of dietary creatine intake from meat protein sources with different types of intestinal problems: insights from NHANES 2005–2010 - Zheng, Baohua; Huang, Zhicheng; Wang, Zhiwei; Du, Junhao; Jiang, Junhui; Xiao, Chunhong; Wang, Yu (Frontiers in Nutrition, 2025)
BackgroundGiven the growing interest in gut health, particularly in the context of irritable bowel syndrome (IBS), this study investigates the potential effects of dietary creatine intake on measures of gut health. Additionally, in response to anecdotal reports on the internet that have not been corroborated by clinical trials, this research examines the relationship between creatine consumption and gastrointestinal outcomes, aiming to address the existing knowledge gap in this area.MethodsThis study utilized data from the 2005–2010 National Health and Nutrition Examination Survey (NHANES). Multivariable logistic regression and subgroup analyses were conducted to examine the association between dietary creatine intake and the risk of diarrhea and constipation. Additionally, restricted cubic spline (RCS) analysis was employed to assess potential nonlinear relationships.ResultsIn the fully adjusted model, each one-unit increase in the log-transformed 2-day average dietary creatine intake—equivalent to a tenfold increase in absolute intake—was associated with a 19% lower risk of chronic constipation (adjusted OR = 0.81, 95% CI: 0.65–0.96, p = 0.015). However, no significant association was found between dietary creatine intake and chronic diarrhea (adjusted OR = 1.04, 95% CI: 0.87–1.36, p = 0.421). The protective effect of higher dietary creatine intake against chronic constipation was more pronounced in males (adjusted OR = 0.77, 95% CI: 0.66–0.89, p < 0.001), younger individuals (adjusted OR = 0.89, 95% CI: 0.79 ∼ 0.99, p = 0.047)), and participants without cardiovascular disease (adjusted OR = 0.91, 95% CI: 0.83 ∼ 0.99, p = 0.047). RCS analysis confirmed a linear relationship between 2-day average dietary creatine intake and the risk of chronic constipation after adjusting for confounding variables.ConclusionHigher dietary creatine intake may offer protective benefits against chronic constipation, particularly in specific subgroups, while showing no significant association with chronic diarrhea. Further large-scale studies are warranted to clarify creatine’s role in gastrointestinal health. These findings highlight the potential of creatine as a dietary factor in promoting gut health.